Characterisation and Bioactivity Analysis of Peridinin-Chlorophyll a-Protein (PCP) Isolated from Symbiodinium tridacnidorum CS-73 - Kanoknate M. Supasri; Manoj Kumar; Anna Segečová; Janice I. McCauley; Andrei Herdean; Matthew P. Padula; Tim O’Meara; Peter J. Ralph (Journal of Marine Science and Engineering, 2021)
Peridinin-Chlorophyll a-Proteins (PCP) are the major light harvesting proteins in photosynthetic dinoflagellates. PCP shows great variation in protein length, pigment ratio, sequence, and spectroscopic properties. PCP conjugates (PerCP) are widely used as fluorescent probes for cellular and tissue analysis in the biomedical field. PCP consists of a peridinin carotenoid; thereby, it can potentially be used as a bioactive compound in pharmaceutical applications. However, the biological activities of PCP are yet to be explored. In this study, we extracted, purified, and partially characterised the PCP from Symbiodinium tridacnidorum (CS-73) and explored its antioxidant, anti-cancer and anti-inflammation bioactivities. The PCP was purified using an ÄKTA™ PURE system and predicted to be of 17.3 kDa molecular weight (confirmed as a single band on SDS-PAGE) with an isoelectric point (pI) 5.6. LC-MS/MS and bioinformatic analysis of purified PCP digested with trypsin indicated it was 164 amino acids long with >90% sequence similarity to PCP of SymA3.s6014_g3 (belonging to clade A of Symbiodinium sp.) confirmed with 59 peptide combinations matched across its protein sequence. The spectroscopic properties of purified PCP showed a slight shift in absorption and emission spectra to previously documented analysis in Symbiodinium species possibly due to variation in amino acid sequences that interact with chl a and peridinin. Purified PCP consisted of a 19-amino-acid-long signal peptide at its N terminal and nine helixes in its secondary structure, with several protein binding sites and no DNA/RNA binding site. Furthermore, purified PCP exhibited antioxidant and in vitro anti-inflammation bioactivities, and anti-cancer activities against human metastatic breast adenocarcinoma (MDA-MB-231) and human colorectal (HTC-15) cancer cell lines. Together, all these findings present PCP as a promising candidate for continued investigations for pharmaceutical applications to cure chronic diseases, apart from its existing application as a fluorescent-probe.